2021
DOI: 10.1177/19322968211064633
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Telemedicine Solutions for the Management of Type 2 Diabetes: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: Background: Previous systematic reviews have aimed to clarify the effect of telemedicine on diabetes. However, such reviews often have a narrow focus, which calls for a more comprehensive systematic review within the field. Hence, the objective of the present systematic review, meta-analysis, and meta-regression is to evaluate the effectiveness of telemedicine solutions versus any comparator without the use of telemedicine on diabetes-related outcomes among adult patients with type 2 diabetes (T2D). Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 524 publications
2
27
0
Order By: Relevance
“…Evidence on the impact of these systems is variable and highly dependent on the embedding of the technology in a more comprehensive approach. Evidence for a beneficial impact of telehealth on achieving treatment goals in those living with type 2 diabetes is growing (333,334).…”
Section: Place Of Technologymentioning
confidence: 99%
“…Evidence on the impact of these systems is variable and highly dependent on the embedding of the technology in a more comprehensive approach. Evidence for a beneficial impact of telehealth on achieving treatment goals in those living with type 2 diabetes is growing (333,334).…”
Section: Place Of Technologymentioning
confidence: 99%
“…Most previous studies on telemedicine for diabetes focused on the effect of telemedicine on the ability to self-manage diabetes [ 12 ], the impact of certain interventions on T2DM self-management [ 13 ] that are not specific to the primary health care setting [ 14 ], and other specific aspects [ 15 ]. Although there have been published reviews of the effectiveness of telemedicine research [ 16 , 17 ] on diabetes, there is a lack of analysis of all the potential outcomes and the impact of telemedicine interventions on patients with type 2 diabetes. In addition, telemedicine has grown rapidly in recent years and new research has emerged, thus requiring an updated review.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kerr et al, 2022 (69) found indications for improved glycemic control when using digital solutions to manage T2D treatment compared to standard of care. This is further supported by Hangaard et al, 2021 (70) , which found a significant improvement in HbA1c when using telemedicine among people with T2D. These studies did not focus on basal insulin titration but overall treatment of people with T2D.…”
Section: Table 2 Summary Of Critical Appraisal Assessed By Jbi Critic...mentioning
confidence: 67%